Ocular Manifestations in Systemic Lupus Erythematosus: A Case Series - Dr. Arpitha K S; Dr. Preethi G; Dr. S Kalpana; Dr. Ramya M (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
The primary purpose of this study is to elucidate the spectrum of ocular manifestations in patients with SLE, emphasizing the importance of early recognition and appropriate management to prevent irreversible vision loss. This case series includes eight patients diagnosed with SLE who presented with various ocular manifestations at a tertiary care center. Patient demographics, clinical presentations, diagnostic evaluations, treatment regimens, and outcomes were documented and analyzed. Diagnostic workups included fundus examinations, slit-lamp assessments, serological testing, and imaging studies when indicated.